Schedule-Dependent Synergy Between the Histone Deacetylase Inhibitor Belinostat and the Dihydrofolate Reductase Inhibitor Pralatrexate in T-and B-cell Lymphoma Cells in vitro - Peters, Godefridus J.; van Gemert, Frank P. A.; Kathmann, Ietje; Reddy, Guru; Cillessen, Saskia A. G. M.; Jansen, Gerrit (Frontiers in Cell and Developmental Biology, 2020)
Pralatrexate (Folotyn; PLX) and belinostat (Beleodaq; BLS) are registered for the treatment of patients with peripheral T-cell lymphoma (PTCL) and have promising activity in other lymphomasIn this study we investigated whether BLS had the ability to potentiate the cytotoxicity of PLX. A panel of lymphoma cell lines was used for the combination studies: the B-cell SUDHL-4, SUDHL-5, HT, Jeko-1 and T-cell Karpas-299 and Hut-78. RFC-mediated uptake efficiency of PLX showed a 6-fold better RFC substrate affinity for PLX compared to methotrexate, and 2-fold better than levo-leucovorin (l-LV). Sensitivity (IC50 concentrations after 72 hr exposure) to PLX varied from 2.8 to 20 nM and for BLS from 100 to to 200 nM, independent of the background of the cell lines. . The interaction between BLS and PLX was studied using the median-drug effect analysis. At a fixed molar ratio between the drugs based on the IC50 concentration the average combination index (CI) for all cell lines showed additivity (CI: ±1.0). In two selected cell lines (SU-DHL-4 and HT) sequential exposure (24 hr pretreatment with either BLS or PLX, followed by 48 hr to PLX + BLS), did not improve interaction (CI: 0.9-1.4). As an alternative approach a non-fixed ratio was used by exposing SU-DHL-4 and HT cells to IC25 concentrations of either BLS or PLX in combination with the other drug. Exposure to IC25 of PLX did not decrease the IC50 for BLS (CI around 1.2), but exposure to IC25 of BLS markedly increased PLX sensitivity (low CIs from 0.40-0.66). Mechanistic studies focused on induction of apoptosis, and showed cleavage of caspase 8 and 9 in HT and SU-DHL-4 cells for both drugs at their IC50s, being similar in the combination setting. Moreover, at these concentrations, the drugs were shown to confer an S-phase arrest. In conclusion, the combination of PLX and BLS showed additivity in various lymphoma cell lines, with a schedule-dependent synergism. Based on these data, proficient inhibition of HDAC activity by BLS holds promise in sensitization of tumor cells to PLX.